The dictionary of modern proverbs - Doyle, Charles Clay 1943- (Yale University Press, 2012)
A volume of English-language proverbs that originated in the twentieth and twenty-first centuries. Entries are organized alphabetically by key words, with information about the earliest datable appearance, origin, history, and meaning of each proverb.